2014
DOI: 10.1093/nar/gku1275
|View full text |Cite
|
Sign up to set email alerts
|

Stress granules are dispensable for mRNA stabilization during cellular stress

Abstract: During cellular stress, protein synthesis is severely reduced and bulk mRNA is recruited to stress granules (SGs). Previously, we showed that the SG-recruited IGF2 mRNA-binding protein 1 (IGF2BP1) interferes with target mRNA degradation during cellular stress. Whether this requires the formation of SGs remained elusive. Here, we demonstrate that the sustained inhibition of visible SGs requires the concomitant knockdown of TIA1, TIAR and G3BP1. FRAP and photo-conversion studies, however, indicate that these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
100
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 41 publications
(122 reference statements)
16
100
0
1
Order By: Relevance
“…For example, translationally repressed mRNAs may have intrinsic properties that cause them to aggregate to form SGs, but the SGs do not have a function in RNA decay per se . In support, one study found that inhibition of SG formation had no effect on mRNA degradation rates [107]. One possibility is that eIF2α phosphorylation—the upstream driver of SG formation—is responsible for inhibiting RNA decay, not SGs themselves.…”
Section: Stress Granules and Rna Degradationmentioning
confidence: 99%
“…For example, translationally repressed mRNAs may have intrinsic properties that cause them to aggregate to form SGs, but the SGs do not have a function in RNA decay per se . In support, one study found that inhibition of SG formation had no effect on mRNA degradation rates [107]. One possibility is that eIF2α phosphorylation—the upstream driver of SG formation—is responsible for inhibiting RNA decay, not SGs themselves.…”
Section: Stress Granules and Rna Degradationmentioning
confidence: 99%
“…Many components of SGs have very short residence times within stress granules (seconds), despite the long-term persistence of the SG itself (minutes to hours), creating challenges to explain these properties (25,26). Posttranslational modifications are commonly found on key SG nucleating proteins; thus, attention is turning to how such modifications may influence SG dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Since they are very dynamic structures where many incorporated proteins quickly exchange with cytoplasmic pools of those proteins (25)(26)(27), posttranslational modifications are implicit in regulating these protein-protein associations. A recent report indicated that the SG nucleating proteins are exchanged more rapidly than those that are incapable of inducing SG aggregation (i.e., ZBP1 and YB1) (25). What regulatory mechanisms promote stress granule disassembly and resumed protein synthesis during the poststress recovery phase is not well understood.…”
mentioning
confidence: 99%
“…crucial for SG assembly (Bley et al, 2015). Moreover, an increase in granule-nucleating proteins stimulates SG production (Kedersha et al, 1999;Tourrière et al, 2003).…”
Section: Ampk Activation Alters Stress Granule Assemblymentioning
confidence: 99%